Hepatic Tissue Engineering Using Scaffolds: State of the Art - Kazemnejad, Somaieh (Avicenna Research Institute, 2009)
Severe hepatic failure accounts for many deaths and raises medical costs each year worldwide. Currently, liver transplantation is the most common therapeutic option for patients with end-stage chronic liver disease. Due to decrease in the number of organ donors, many in need of transplantation continue to remain on the waiting list. Hepatic Tissue Engineering is a step toward alleviating the need for organ donors. Regenerative medicine and tissue engineering require two complementary key ingredients as follows: 1) biologically compatible scaffolds that can be readily adopted by the body system without harm, and 2) suitable cells including various stem cells or primary cells that effectively replace the damaged tissues without adverse consequences. Yet many challenges must be overcome such as scaffold choice, cell source and immunological barriers. Today, hepatogenic differentiation of stem cells has created trust and promise for use of these cells in hepatic tissue engineering and liver replacement. However, using suitable scaffolds is an important key to achieving the necessary functions required for hepatic replacement. In recent years, different scaffolds have been used for liver tissue engineering. In this review, we have presented different concepts in using cell /scaffold constructs to guide hepatic tissue engineering.